Student’s Perception On Implementation Of Evidence Based Practice In Clinical Practice - Hafidz Triantoro Aji Pratomo (Jurnal Keterapian Fisik, 2021)
Background: Evidence Based Practice (EBP) is an important component in clinical practice of a Speech Therapist. Students can develop critical thinking pattern using credible literature. The sustainable implementation of EBP can improve practical quality of Speech Therapist, particularly in clinical decision making. EBP use in speech therapy clinical setting has been unknown in Indonesia. This research aims to identify the implementation of EBP by speech therapy students in clinical setting. Methods: The respondents employed in this study consisted of 35 students. The research was conducted using survey method. Survey was distributed online using Google form application. Sample comprised last-year students of Speech and Language Therapy Applied Bachelor Study Program. The students were those who have undertaken clinical practice in hospital, clinical, or other healthcare service facilities. Analysis was conducted descriptively with correlational analysis technique. Results: Descriptive analysis shows that students’ perceptions are varying. Inter-variable cororelation was analyzed using correlation test. The result of analysis shows coefficient of correlation (r) > 0.2, meaning that there is a correlation between case experience, EBP level knowledge, knowledge on EBP, speech therapist’s attitude and role, and EBP implementation Conclusion: Survey informs that scientific literacy culture is still weak. This study found the correlation between experience, knowledge, attitude, and EBP implementation. In-depth investigation is required on the different data appearing.